Labour market effects of digital matching platforms: Experimental evidence from sub-Saharan Africa - Sam Jones; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Can digital labour market platforms reduce search frictions in either formal or informal labour markets? We study this question using a randomized experiment embedded in a tracer study of the work transitions of graduates from technical and vocational colleges in Mozambique. We implement an encouragement design, inviting graduates by SMS to join one of two local digital platforms: Biscate, a site to find freelancers for informal manual tasks; and Emprego, a conventional formal jobs website. In contrast to positive estimates of the contribution of both platforms to job outcomes from naïve (per-treatment) estimates, both intent-to-treat and complier average treatment effects are consistently zero in the full sample, while the impact on life satisfaction is negative. However, use of the informal jobs platform leads to better work outcomes for women, especially those with manual qualifications, for whom earnings rise by over 50 per cent.
Keywords: J46; J64; J68; O15; 330; digital labour platforms; search frictions; technical and vocational education; unemployment; Mozambique